Three-Dimensional Collagen Membranes Challenging the Gold Standard in Gingival Recession - Siddharth Narayan; G Kaarthikeyan (Wolters Kluwer Medknow Publications, 2023)
Gingival recession is a commonly encountered chief complaint in a dental office, most commonly presenting as pain or sensitivity on intake of food or sometimes just seen as an esthetic concern which may present in a localized or generalized form. Such interest toward dental esthetics has encouraged clinicians to formulate newer minimally invasive surgical techniques which are short but still deliver predictable long-term benefits in restoring the patient's smile. One such method was evaluated in the present short communication where a commercially available, biodegradable, and volume-stable collagen membrane was used to manage gingival recession instead of donor grafts. The clinical parameters which were assessed after a period of 9 months demonstrated an increased width of attached gingiva and overall tissue thickness after surgical intervention. These findings along with successful mean root coverage of the upper left canine would seem to challenge the results obtained while using similar procedures and donor grafts, the age-old gold standard bio-filler. The dawn of esthetic dentistry is here with more emphasis on how physical appearance bolsters confidence and morale among younger individuals. Among the various complaints concerned with patient's esthetic, periodontal plastic surgery is one of the more challenging procedures. The real obstacle while performing such procedures is achieving complete or partial root coverage over an avascular bed, whereas multiple variables seem to affect the overall clinical outcome.